2023
DOI: 10.1177/23969873231205669
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic significance of intracranial atherosclerotic disease and ipsilateral imaging markers of cerebral small vessel disease

Lina Zheng,
Xuan Tian,
Jill Abrigo
et al.

Abstract: Introduction: Cerebral small vessel disease (CSVD) commonly exists in patients with symptomatic intracranial atherosclerotic disease (sICAD). We aimed to investigate the associations of hemodynamic features of sICAD lesions with imaging markers and overall burden of CSVD. Patients and methods: Patients with anterior-circulation sICAD (50%–99% stenosis) were analyzed in this cross-sectional study. Hemodynamic features of a sICAD lesion were quantified by translesional pressure ratio (PR = Pressurepost-stenotic/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Correlations with cerebral small vessel disease in crosssectional study Cerebral small vessel disease (CSVD) commonly coexists with ICAS, particularly in older individuals. 23 In a crosssectional study, Zheng et al 24 associated abnormal PR (PR≤median) and WSSR (WSSR≥fourth quartile) with moderate-to-severe white matter hyperintensities (aOR: 10.12, p=0.018), presence of cortical microinfarcts (aOR: 5.25, p=0.003) and moderate-to-severe overall CSVD burden (aOR: 12.55, p=0.033) in the ipsilateral hemisphere to sICAS, independent of these CSVD imaging markers and overall burden in the contralateral hemisphere. The study indicated the role of haemodynamics in affecting the severity of CSVD in patients with sICAS.…”
Section: Correlations With Collateral and Perfusion Status In Crossse...mentioning
confidence: 99%
“…Correlations with cerebral small vessel disease in crosssectional study Cerebral small vessel disease (CSVD) commonly coexists with ICAS, particularly in older individuals. 23 In a crosssectional study, Zheng et al 24 associated abnormal PR (PR≤median) and WSSR (WSSR≥fourth quartile) with moderate-to-severe white matter hyperintensities (aOR: 10.12, p=0.018), presence of cortical microinfarcts (aOR: 5.25, p=0.003) and moderate-to-severe overall CSVD burden (aOR: 12.55, p=0.033) in the ipsilateral hemisphere to sICAS, independent of these CSVD imaging markers and overall burden in the contralateral hemisphere. The study indicated the role of haemodynamics in affecting the severity of CSVD in patients with sICAS.…”
Section: Correlations With Collateral and Perfusion Status In Crossse...mentioning
confidence: 99%
“…[44][45][46] Apart from clinical strokes, covert brain infarcts in the forms of lacunes and subcortical or cortical infarcts/microinfarcts are common findings among patients with LAD and AF and are recognized as substrates for cognitive impairment. [47][48][49][50] Moreover, chronic microemboli and hypoperfusion from LAD and cardiac diseases may contribute to cognitive decline. Impaired cerebral hemodynamics was independently associated with cognitive decline in patients with steno-occlusive disease of carotid arteries without a history of stroke.…”
Section: Covert Brain Infarcts and Chronic Hypoperfusion Due To Large...mentioning
confidence: 99%